The Effect of Locomotor Training on Gait Parameters in Pediatric Patients with Cerebral Palsy: a Systematic Review and Meta-analysis - Emilija Strazdaitė; Dovilė Kielė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Locomotor training is a relatively new approach in pediatric cerebral palsy, so there is still a lack of data on its effect of such training on walking function.